Seaplane on Lake Union during Golden Potlatch, Seattle, July 1914 - Nowell, Frank H.
The Golden Potlatch was a city-wide festival held in July, organized by civic boosters hoping to capitalize on the success of the Alaska-Yukon-Pacific Exposition. The first Golden Potlatch opened in July 1911; the event continued for each of the next three summers before being suspended during wartime. The name reflects the importance of the Klondike gold rush to Seattle and borrows a Chinook jargon term for a gift-giving ceremony. The boosters also used Chinook jargon to call themselves the Tillikums (friend) of Elttaes, (Seattle spelled backward). Thousands of people enjoyed the week-long carnival of parades, aircraft demonstrations and concerts. In this photo, a crowd surrounds the seaplane "Tilikum" on the shores of Lake Union for a christening ceremony. Aviator Silas Christofferson thrilled spectators by flying the "Tilikum" to demonstrate air warfare, dropping flour bombs over downtown Seattle. Embossed on front of print: Frank H. Nowell, U.S.A. Photo from album with "Tillikums of Elttaes" embossed on the cover. Caption information source: The Seattle Daily Times, July 15, 1914, p. 2 and July 19, 1914, p. 1. 1 photographic print: b&w; 9 5/8 x 7 3/4 in.